STCAFormer: Spatio-temporal cross attention based transformer for fusion of remote sensing images - Jun Li; Xiaowei He; Yantai Yang; Qinghong Sheng; Zhaocong Wu; Bo Wang; Xiao Ling; Xiang Liu; Yu Liu; Fan Gao; Libo Wang; Matthieu Molinier (Remote Sensing of Environment, 2026)

Stochastic analysis of horizontal dynamic response of offshore pipe piles considering hydrodynamic pressure - Bo Yu; Libo Chen; Guang Han; Lichen Li; M. Hesham El Naggar; Wenbing Wu (Ocean Engineering, 2026)

Buffer zones concentrate conflicts but enable effective management: Rethinking spatial separation in conservation - Yu Shen; Bin Liu; Xiaoping Sun; Libo Wang; Dandan Xue; Yijun Ren; Kaimei Zhang (Global and Planetary Change, 2026)

Study on the improvement effect of water-based polyurethane/cellulose acetate composite on silty clay for slope ecological restoration in seasonally frozen soil regions - Xinhao Wu; Chenglong Yu; Libo Liu; Huanan Liu; Jiquan Zhang; Yichen Zhang; Qinze Du; Haoxin Chen (Ecological Engineering, 2026)

Effects of plant hedges and slope terraces on soil degradation on sloping farmland in the Chinese black soil region - Linhui Zhou; Libo Ye; Jialong Wu; Yu Zhang; Haiou Shen; Hongli Li (Ecological Engineering, 2026)

A dual-mode wearable sensor based on a metal dendrites incorporated electrospun membrane - Chen Xu; Mengjie Si; Yueman Tang; Libo Zhang; Chen Yu Li; Yan-Jie Wang; Hongyao Ding; Si Yu Zheng; Jintao Yang (Chemical Engineering Journal, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Construction of 3DOM TiO2/CuO S-scheme heterostructures with tuned oxygen vacancies for high-performance photocatalytic U(VI) sequestration from wastewater - Yuxiang Deng; Zhenyu Cai; Libo Yang; Zhiyao Wu; Bihong Chen; Chang Gao; Xinyu Yu; Nannan Wang; Xinpeng Wang (Chemical Engineering Journal, 2026)

Interfacial energy homogenization enables β-phase transition and high piezoactivity in MOF/PVDF membrane for sustainable pollutant degradation - Zi Yang; Miaomiao Tian; Cheng Chen; Zhiyu Zhao; Libo Zhao; Jiujing Xu; Wei Yu; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Simultaneous multiple gastrointestinal perforations in adults: A systematic review of 133 cases - Libo Feng; Dong Xia; Yu Liu (Next Research, 2026)

Folate enrichment of soymilk by Lactiplantibacillus plantarum D15-04: Strain screening, fermentation optimization, product characterization, and changes during refrigerated storage - Tian Liu; Congxin Dong; Ruxue Yu; Chun Li; Guofang Zhang; Libo Liu; Liying Wang; Peng Du (Food Bioscience, 2026)

Chemo-mechanical deterioration of oolitic limestone in simulated rhizosphere environments: Differential weathering and shielding mechanisms - Yu Zhou; Naize Jia; Xiangjun Pei; Qinyuan Liang; Qiongqiong Tang; Guansheng Han; Libo Zheng (Engineering Geology, 2026)

Study of vibration and acoustic control of outboard propulsion motors - Yuxiang Li; Libo Qi; Zeyang Li; Yue Yu; Hao Li (Ocean Engineering, 2026)

Lactobacillus helveticus KLDS 1.1105 postbiotics alleviate functional constipation through gut microbiota modulation - Jiaying Liu; Miao Li; Qi Xin; Chun Li; Aili Li; Guofang Zhang; Ruihong Yu; Peng Du; Libo Liu (Food Bioscience, 2026)

Formation, evolution, and habitability of terrestrial planets: A review of research progress - Yuming Wang; Jianzhong Liu; Libo Liu; Liping Qin; Yang Li; Zhenpeng Su; Lihui Chai; Xuan Fang; Jianqiao Xu; Bing Yang; Wei Yang; Zongyu Yue; et al. (Science China Earth Sciences, 2026)

Investigation into the Distribution Characteristics and Sources of Dissolved Gases in the Offshore Waters of Dingzi Bay, South Yellow Sea - Jingtao Zhao; Xuebo Yin; Kaixin Yu; Zhenfei He; Kuiying Zhang; Fuyu Wu; Jing Kan; Libo Wang; Hao Tian; Yong Zhang (Journal of Marine Science and Engineering, 2026)
Utilizing seawater samples collected during the summer of 2025 in the Dingzi Bay region, South Yellow Sea, this study conducted a comprehensive analysis of the contents and concentrations of dissolved gases (N2, O2, Ar, CO2) and hydrocarbon gases (such as methane, ethane, and propane). The findings reveal that the dissolved gases in the study area are predominantly composed of N2 and O2, with average proportions of 77.8% and 21.6%, respectively. Notably, significant CO2 anomalies were detected at certain stations, which may indicate intense organic matter degradation or the introduction of external fluids. Furthermore, wet gas constituents, including propane, butane, and isobutane, were identified in several samples, suggesting potential submarine oil and gas seepage or subsurface thermogenic gas input. Spatial analysis revealed that anomalous points were primarily concentrated at stations CJ01, CJ08, CJ10, and CQ01, with no significant correlation to water depth, suggesting that their distribution may be influenced by local geological structures or bottom currents. This study elucidates the complexity and heterogeneity of dissolved gas composition in the waters of Dingzi Bay, thereby providing a novel scientific foundation for regional carbon cycle research, seabed resource exploration, and marine environmental monitoring.

Rapid behavioral regulations facilitate the formation of a novel migration route in swan geese - Zhongru Gu; Juan Long; Xinying Shi; Xin Liu; Zhuoran Kuang; Zhenyu Zhong; Jiade Bai; Zhibin Cheng; Nyambayar Batbayar; Batbayar Bold; Libo Zhou; Junfeng Chen; et al. (Science Bulletin, 2026)

An ultra-stretchable, tough yet resilient hydrogel with high fatigue fracture threshold - Changpeng Wang; Hongyao Ding; Yuming Deng; Libo Zhang; Runjie Zhai; Hui Li; Si Yu Zheng (Chemical Engineering Journal, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

CardioNVT: an AI platform for immunostaining-free, high-throughput cardiomyocyte ploidy assessment in situ - Zehao Yao; Lina Bai; Zhongkai Luo; Yuan Liu; Lingfang Chen; Minjiong Zhao; Youzhi Sun; Libo Zhang; Yu Nie (Science Bulletin, 2026)

AI-guided discovery of an efficient chitinase enables green production of chitobioses with distinct cadmium stress-alleviating efficacy in rice - Youbo Yu; Jin Huang; Wei Wang; Jielin Tian; Li Yang; Lisha Yan; Liping Zhan; Janaki Mohotti; Liang Hong; Pan Tan; Gefei Hao; Libo Zhang (Chemical Engineering Journal, 2026)

GMFB promotes lung adenocarcinoma progression by activating the MAPK/ERK signaling pathway - Luyuan Ma; Jiacheng Li; Wenhao Yu; Rongyang Li; Libo Si (Molecular and Cellular Biochemistry, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Thermal-mechanical coupled vibration characteristics of a rotating FGP-GNPRC stepped cylindrical shell in nonlinear thermal environment - Ziyi Wang; Hui Li; Yufeng Chang; Qingpeng Han; Ze Jian; Yu Wang; Libo Cai (Engineering Structures, 2026)

Effects of Electrochemical Desalination Cycles on the Stability of Bound Chloride Ions Under Combined Chloride–Sulfate Attack - Libo Yu; Hongqiang Chu; Linhua Jiang; Hao Dong (Journal of Marine Science and Engineering, 2026)
Corrosion of reinforcing steel exposed to chloride leads to the degradation of steel-reinforced concrete structures. Electrochemical chloride removal (ECR) has proven to be a non-destructive and cost-effective rehabilitation technique for reinforced concrete structures. Most studies have focused on chloride attack, with free chloride removal efficiency used as the primary index to measure ECR performance. Hence, we focused on the influence of ECR on bound chloride ions under the combined effect of chloride and sulfate. The instability of bound chloride ions was investigated through macroscopic experiments, whereas the underlying mechanism was revealed using XRD and TG-DTG analyses. In addition, a three-dimensional ECR simulation was developed using the finite element method. Both free and bound chloride ion concentrations decreased over the experimental period, with the rate of decrease being higher during the first 4 weeks than during the subsequent 4 weeks. The decomposition of C–S–H gel and the desorption of physically adsorbed chloride ions played a leading role in the release of bound chloride ions, whereas the contribution of Friedel’s salt was comparatively minor. The three-dimensional finite element simulation demonstrated that ECR can effectively remove chloride ions from concrete and that the longer the treatment time, the greater the effect.

Inhibitory control occurs at the language execution stage: evidence from an fMRI study of bilingual language switching - Libo Geng; Hongyi Yu; Shengwei Liu; Peng Wang; Keqing Shao; Yiming Yang (Brain Imaging and Behavior, 2026)

PFAS-induced immunotoxicity in freshwater fish of inland China: mechanisms and ecological risks - Helei Cai; Qizhuan Lin; Changyong Gong; Fan Yu; Libo Jin; Renyi Peng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Pore channel regulation via organic amine-modified 13X zeolite for CO2 capture from C2H2 - Xinyue Yu; Bairui Li; Bin Zhang; Jiawei Wang; Xiufeng Shi; Libo Li (Journal of Environmental Chemical Engineering, 2025)

Station-aware heating, ventilation, and air conditioning energy prediction in urban rail transit via mixture of experts - Wei Zhang; Hui Fang; Fan Yang; Chaoqun Wang; Tongle Wu; Libo Xu; Jiajun Bu; Qiming Zhong; Yueyao Yu (Energy and Buildings, 2025)

Boosting power output of NH3BH3 fuel cell by modulating H* and OH− adsorption via Cu@Pd core-shell structured nanowire arrays - Shuo Bi; Libo Zhu; Han Tian; Fantao Kong; Xu Yu; Qin Li; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

Synergistic catalysis of multi-metallic acid–base sites on tea residue-derived biochar for efficient glucose isomerization - Baoting Yi; Huimei Wang; Pan Deng; Xiaohui Wang; Keyin Liu; Xingjie Wang; Fangong Kong; LiBo Li; Junli Ren; Yu Liu (Journal of Environmental Chemical Engineering, 2025)

AIM2-PANoptosome-driven PANoptosis in hepatic lipid dysregulation induced by β-HCH and nanoplastics co-exposure - Qizhuan Lin; Helei Cai; Fan Yu; Changyong Gong; Yize Wu; Qiufang Wu; Feiqin Xie; Wenhui Xu; Shihua Chen; Xinxin Yao; Libo Jin; Renyi Peng (Apoptosis, 2025)

Life Cycle Assessment of Kitchen/Agricultural Waste Hydrothermal Conversion For Bio-Oil Production - Libo Zhang; Xinyu Yu; Jianing Wang; Jiachen Zuo (BioEnergy Research, 2025)

The miR-122/P53/TIGAR signaling axis regulates glucose metabolic reprogramming induced by polystyrene nanoplastic particles - Ting Chen; Changyong Gong; Fan Yu; Helei Cai; Xinxin Yao; Shihua Chen; Qiufang Wu; Yize Wu; Wenhui Xu; Feiqin Xie; Libo Jin; Renyi Peng (Journal of Hazardous Materials, 2025)

Safety evaluation of Bifidobacterium pseudocatenulatum E−0810 and its synbiotic formulation with xylooligosaccharides in alleviating LPS-induced inflammation in intestinal epithelial cells - Zhenyu Yang; Xinyu Wang; Shan Wu; Yu Xin; Peng Du; Guofang Zhang; Chun Li; Libo Liu (Food Bioscience, 2025)

Integrating computer vision and machine learning technologies for model building to quantify intermuscular fat content in salmonid fillets - Ming Huang; Libo Wang; Boyuan Wang; Wenxin Jiang; Yining Yu; Qingkai Tang; Qinfeng Gao; Yuan Tian (Food Control, 2025)

Effect of plant elicitor Isotianil on the rhizosphere soil microbiome composition of banana cultivars with different resistance to Fusarium wilt - Wenlong Zhang; Guangdong Zhou; Ping He; Hongwei Yu; Libo Tian; Yun-Yue Wang; Si-Jun Zheng (Plant and Soil, 2025)

Differential Resting-State Brain Activity Following Early- and Late-Night Sleep Loss - Tianqi Di; Libo Zhang; Shiqiu Meng; Yang Guo; Wangyue Liu; Enyu Zheng; Zhoulong Yu; Yan Sun; Jie Shi (Neuroscience Bulletin, 2025)

Sustainable hydrogen production from coal tar residue via supercritical water gasification - Jingui Bai; Yu Wang; Shi Liu; Libo Lu; Wen Cao; Ting Chen; Yunan Chen; Liejin Guo (Journal of Cleaner Production, 2025)

Removal of copper and cadmium from industrial zinc sulfate leachates by ultrasonic enhanced zinc powder - Yingjie Xu; Ningting Li; Bo Yang; Hongying Xia; Xudong Li; Kan Yu; Hao Yang; Libo Zhang (Journal of Environmental Chemical Engineering, 2025)

NlAgo3 and NlBiwi are essential for piRNAs biogenesis and female reproduction in Nilaparvata lugens - Shengli Jing; Jingang Xu; Fang Zheng; Jianfeng Jin; Xiaoyan Huang; Libo Mao; Feifei Wang; Hanmo Zhang; Jingwen Xu; Jing Yang; Ruixian Chen; Bin Yu; et al. (Insect Biochemistry and Molecular Biology, 2025)

An iontronic pressure sensor with high linearity and ultrawide range over 4 MPa for submarine pressure monitoring - Menghui Xiang; Longfei Yu; Jin Chai; Yusheng Lei; Yunlong Zhao; Guirong Wu; Junyang Li; Chenyang Xue; Libo Gao (Chemical Engineering Journal, 2025)

Interaction of osteopontin with α-lactalbumin and their synergistic effects in protecting intestinal barrier injury - Wanfu He; Xinyu Wang; Jiayi Zhang; Hongfang Cao; Shuai Ren; Xinyao Sun; Haiying Yu; Guofang Zhang; Chun Li; Libo Liu; Caiyun Wang; Jian He (Food Research International, 2025)

Strength prediction and uncertainty quantification of welded CHS tubular joints via Gaussian process regression - Bowen Chen; Libo Chen; Ruchun Mo; Zongcheng Wang; Li Zheng; Canlin Zhang; Yu Chen (Engineering Structures, 2025)

Ecological diversity and metabolic strategies of widespread Marinisomatota in global oceans - Shizheng Xiang; Jianyang Li; Zhen Chen; Ruolin Cheng; Liping Wang; Libo Yu; Guangshan Wei; Xiangyu Guan; Brandon R. Briggs; Gary King; Hongchen Jiang; Zongze Shao (Marine Life Science & Technology, 2025)

Numerical Investigations of a Column Configuration with Towed Super Long Cable in Underwater Environment - Xiaopeng Xue; Yue Yu; Danjun Zhao; Degui Yang; Libo Qi (Journal of Marine Science and Engineering, 2025)
In the present study, a simple immersion boundary method was developed to numerically simulate the fluid-structure-acoustic coupling problem of underwater vehicles and their towed super long cables. A typical underwater vehicle connected with different cable models at different positions was created in this study. The length of the vehicle is 4356 mm, the cables are approximately 4 and 6 times the vehicle length, i.e., 17,424 mm and 26,136 mm, and the freestream velocity is 7.72 m/s (15 kts). In the simulation, the freestream velocities are 9.26 m/s (18 kts), 7.72 m/s (15 kts), and 5.14 m/s (10 kts), respectively. The models are numerically simulated by a simple immersion boundary method to solve the flow field structure, the velocity profile, and the transverse flow near the towed cable, compute the pressure pulsation of the cable models with huge lengths and extremely small diameters, and analyze their flow noise. The results show that the towed cables with different lengths have a relatively small impact on the velocity distribution around the underwater vehicle system; however, the transverse flow occurs near the cable, thereby affecting the pressure pulsation changes and causing significant flow noise problems. Furthermore, it was also found that the closer the connection position of the towed cable is to the center position, the more significant the impact on the downstream flow fields and the higher the sound pressure level of the flow noise.

Spatial distributions, potential sources, and ecological risks of heavy metals in stream sediments in Zambia - Hongwei Sun; Junping Ren; Jie Wang; Jianzhong Yu; Libo Zuo; Xingyuan Wu; Chipilauka Mukofu; Alphet Phaskani Dokowe; Shuping Cao; Xujiang Cheng (Journal of Geochemical Exploration, 2025)

Ultrasound-assisted fermentation effectively alleviates the weakening of wheat gluten network caused by long-chain inulin and the underlying mechanism - Chonghui Yue; Yu Tang; Ziying Li; Xin Wang; Libo Wang; Denglin Luo; Peiyan Li; Sihai Han; Jinying Guo; Zhouya Bai (Food Research International, 2025)

Trade-offs between agronomic and environmental benefits: A comparison of inhibitors with controlled release fertilizers in global maize systems - Minyu Wang; Ping He; Daijia Fan; Rong Jiang; Guoyuan Zou; Daping Song; Libo Zhang; Yu Zhang; Wentian He (Field Crops Research, 2025)

Evaluations of two ion temperature models in IRI-2020 based on the observations from ICON and COSMIC-2 IVM - Tingwei Han; Huijun Le; Shun-Rong Zhang; Vladimir Truhlik; Natalie Reeves; Angkita Hazarika; Yujin Cho; Mei-Yu Chen; Libo Liu; Yiding Chen; Ruilong Zhang (Advances in Space Research, 2025)

Bee venom peptide Anoplin conjugates as antibacterial agents for both Gram-positive and Gram-negative bacteria - Libo Yuan; Lei Lei; Yu Zhang; Yuan Fang; Kui Lu (Toxicon, 2025)

Deterministic quantum state and gate teleportation between distant superconducting chips - Jiawei Qiu; Yang Liu; Ling Hu; Yukai Wu; Jingjing Niu; Libo Zhang; Wenhui Huang; Yuanzhen Chen; Jian Li; Song Liu; Youpeng Zhong; Luming Duan; et al. (Science Bulletin, 2025)

Mitochondrial homeostatic imbalance-mediated developmental toxicity to H2S in embryonic zebrafish - Yinai Liu; Yu Cao; Huiqi Li; Huanpeng Liu; Ting Chen; Qizhuan Lin; Changyong Gong; Fan Yu; Helei Cai; Libo Jin; Renyi Peng (Environmental Pollution, 2025)

Correction to: Desiccation-induced cracking and deformation characteristics in compacted loess: insights from electrical resistivity and microstructure analysis - Pengju Qin; Yao Geng; Yu Lu; Libo Mao; Jun Zhang (Bulletin of Engineering Geology and the Environment, 2025)

A systemic review of yak milk and its products on the Qinghai-Tibet Plateau: Unique products, chemical composition, biological activities, and microbial composition - Zhiqiang Liang; Xiaoqian Chen; Xinyu Wang; Xiaoxi Qi; Lina Zhang; Yu Xin; Zhenyu Yang; Rui Fan; Yang Li; Libo Liu; Chun Li (Trends in Food Science & Technology, 2024)

Silver nanoparticles stabilized by cranberry polyphenols exhibited enhanced protective effects against hemolysis and preservative effects on fresh blueberries - Libo Wang; Yushun Wang; Zhe Chen; Ling Zhu; Dong Qin; Yu Yang; Yaqin Xu (Food Bioscience, 2024)

Desiccation-induced cracking and deformation characteristics in compacted loess: insights from electrical resistivity and microstructure analysis - Pengju Qin; Yao Geng; Yu Lu; Libo Mao; Jun Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Deciphering the roles of nitrogen source in sharping synchronous metabolic pathways of linear alkylbenzene sulfonate and nitrogen in a membrane biofilm for treating greywater - Ying Liu; Anqi Dai; Libo Xia; Yu Zhou; Tian Ren; Yi Huang; Yun Zhou (Environmental Research, 2024)

Immunomodulatory potential of Lactobacillus helveticus KLDS 1.8701 postbiotics: By regulating the Th17/Treg balance - Yu Xin; Chengwen Hu; Yang Li; Zhenyu Yang; Lina Zhang; Aili Li; Chun Li; Libo Liu; Peng Du (Food Bioscience, 2024)

Improvement of mechanochemical leaching of zinc oxide ore — Optimization of grinding parameters for basket grinder - Yusen Yu; Lixue Cui; Libo Zhang; Yunfan Wang (Journal of Cleaner Production, 2024)

Effect of exogenous protein substitution in glutinous rice cake: Batter rheology, structure, and retrogradation behavior - Yingnan Liu; Shulei Yu; Pengfei Jiang; Baoshang Fu; Libo Qi; Shan Shang (Journal of Cereal Science, 2024)

Analysis of flavor substances changes during fermentation of Chinese spicy cabbage based on GC-IMS and PCA - Wenkui Guo; Meiru Cheng; Xuemei Dong; Chuan Liu; Yu Miao; Peng Du; Hong Chu; Chun Li; Libo Liu (Food Research International, 2024)

Deterioration pattern of the axial compressive properties of steel-reinforced concrete columns owing to chloride salt erosion - Zhiquan Xing; Yi Guo; Yao Zhu; Libo Chen; Kwok-Fai Chung; Yu Chen (Engineering Structures, 2024)

Understanding the links between micro/nanoplastics-induced gut microbes dysbiosis and potential diseases in fish: A review - Yu Cao; Liuliu Bi; Qianqian Chen; Yinai Liu; Haiyang Zhao; Libo Jin; Renyi Peng (Environmental Pollution, 2024)

Investigating the regional ecological environment stability and its feedback effect on interference using a novel vegetation resilience assessment model - Jiping Yao; Guoqiang Wang; Ruihong Yu; Jie Su; Yinglan A; Xiaojing Zhang; Libo Wang; Qingqing Fang (Science of The Total Environment, 2024)

Investigating the cooling effects of land cover and landscape patterns surrounding rivers: Insights from the subtropical city of Changsha, China - Jie Tan; Wenjun Kuang; De Yu; Weijun Zhou; Xigui Li; Qin Liu; Libo He (Urban Climate, 2024)

Unlocking the mystery of Tibetan yak butter and its byproducts: Processing, physicochemical characteristics, functional benefits, and applications - Guofang Zhang; Jinwei Sun; Jingbo Yang; Xiaoxi Qi; Ramnarain Ramakrishna; Qiming Li; Wengkui Guo; Chun Li; Libo Liu; Peng Du; Wei Yu; Bingcan Chen (Trends in Food Science & Technology, 2024)

Isolation and Characterization of Paracoccus maritimus sp. nov., from Intertidal Sediment - Libo Yu; Guangxin Xu; Shiping Wei; Qiliang Lai; Zongze Shao (Current Microbiology, 2024)

Light on multi-mode optical properties of carbon dots through rational surface engineering tuning strategies - Runfang Pei; Pinyi He; Fu Qin; Jianlong Ma; Cuixing Xu; Libo Qin; Wei Gao; Chun Han; Xinyu Wang; Xu Yu; Jianliang Bai; Zhijun Wang; et al. (Chemical Engineering Journal, 2024)

Experimental investigation on the supercritical water gasification of coal by integrating the hydrogen oxidation process into a supercritical water fluidized bed - Kui Luo; Chenchen Zhou; Yu Wang; Zhiyong Peng; Libo Lu; Hui Jin; Liejin Guo (Fuel, 2024)

Discrepant assembly processes of prokaryotic communities between the abyssal and hadal sediments in Yap Trench - Chongran Sun; Shuangfei Zhang; Jichao Yang; Hongbo Zhou; Haina Cheng; Zhu Chen; Libo Yu; Yuguang Wang; Xinhua Chen (Environmental Research, 2024)

Sodium nitroprusside alleviates nanoplastics-induced developmental toxicity by suppressing apoptosis, ferroptosis and inflammation - Qianqian Chen; Yu Cao; Huiqi Li; Huanpeng Liu; Yinai Liu; Liuliu Bi; Haiyang Zhao; Libo Jin; Renyi Peng (Journal of Environmental Management, 2023)

The potential of white-rot fungi for algal control: Mechanisms, Strategies, and Challenges - Haiyang Yu; Pengyu Lei; Jiahui Ma; Jiahui Jin; Yilei Ma; Yimeng Fang; Guoming Zeng; Kun Zhang; Libo Jin; Da Sun (Environmental Research, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Engeletin alleviates erastin-induced oxidative stress and protects against ferroptosis via Nrf2/Keap1 pathway in bone marrow mesenchymal stem cells - Lei Huang; Mengxuan Bian; Shunyi Lu; Jiayi Wang; Jieqin Yu; Libo Jiang; Jian Zhang (Tissue and Cell, 2023)

Diverse changes in shipping emissions around the Western Pacific ports under the coeffect of the epidemic and fuel oil policy - Yupeng Yuan; Yan Zhang; Jingbo Mao; Guangyuan Yu; Kai Xu; Junri Zhao; Haoqi Qian; Libo Wu; Xin Yang; Yingjun Chen; Weichun Ma (Science of The Total Environment, 2023)

Identification and expression of the CCO family during development, ripening and stress response in banana - Liming Zeng; Liwang Zeng; Yu Wang; Zhengnan Xie; Minhua Zhao; Jie Chen; Xiaoxue Ye; Weiwei Tie; Meiying Li; Sang Shang; Libo Tian; Jian Zeng; et al. (Genetica, 2023)

Effect of chlorogenic acid on lipid metabolism in 3T3-L1 cells induced by oxidative stress - Libo Liu; Chenyi Zhang; Min Zhai; Tianshu Yu; Mengqi Pei; Peng Du; Aili Li; Jiayi Yan; Chun Li; Guofang Zhang (Food Bioscience, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Orientin downregulating oxidative stress-mediated endoplasmic reticulum stress and mitochondrial dysfunction through AMPK/SIRT1 pathway in rat nucleus pulposus cells in vitro and attenuated intervertebral disc degeneration in vivo - Zhao Zhang; Jingtao Wu; Cheng Teng; Jinquan Wang; Jiapei Yu; Chen Jin; Libo Wang; Long Wu; Zhen Lin; Ziping Yu; Zhongke Lin (Apoptosis, 2022)

Inhibition of NLRP1-Dependent Pyroptosis Prevents Glycogen Synthase Kinase-3β Overactivation–Induced Hyperphosphorylated Tau in Rats - Xiangying Liu; Wenjing Song; Ying Yu; Jianhua Su; Xiaoyan Shi; Xin Yang; Honghui Wang; Peng Liu; Libo Zou (Neurotoxicity Research, 2022)

Measurement of Martian atmospheric winds by the O2 1.27 μm airglow observations using Doppler Michelson Interferometry: A concept study - Na Yang; Chunliang Xia; Tao Yu; Xiaomin Zuo; Yangyi Sun; Xiangxiang Yan; Jian Zhang; Jin Wang; Huijun Le; Libo Liu; William Edmund Ward (Science China Earth Sciences, 2021)

Halomonas sedimenti sp. nov., a Halotolerant Bacterium Isolated from Deep-Sea Sediment of the Southwest Indian Ocean - Xu Qiu; Libo Yu; Xiaorong Cao; Huangming Wu; Guangxin Xu; Xixiang Tang (Current Microbiology, 2021)

Phylogenomic analysis reveals a two‐stage process of the evolutionary transition of Shewanella from the upper ocean to the hadal zone - Xixiang Tang; Libo Yu; Yi Yi; Jiahua Wang; Siyuan Wang; Canxing Meng; Shunzhang Liu; Yali Hao; Yue Zhang; Xiaorong Cao; Huahua Jian; Xiang Xiao (Environmental Microbiology, 2021)
Summary Shewanella strains are characterized by versatile metabolic capabilities, resulting in their wide distribution in the ocean at different depths. Considering that particle sedimentation is an important dynamic process in the ocean, we hypothesized that hadal Shewanella species evolved from the upper ocean. In this study, we isolated three novel Shewanella strains from deep‐sea sediments in the Southwest Indian Ocean. Genome sequencing indicated that strains YLB‐06 and YLB‐08 represent two novel species in the genus Shewanella . Through phylogenomic analysis, we showed that speciation and genomic changes in marine Shewanella strains are related to water depth. We further confirmed the aforementioned hypothesis and revealed a two‐stage process of the evolutionary transition of Shewanella from the upper ocean to the hadal zone by comparative genomics and gene gain/loss analysis. Finally, the transcriptomic analysis demonstrated that recently obtained genes are strictly repressed and may thus play a minor role in the response to environmental changes.

Bacillus yapensis sp. nov., a novel piezotolerant bacterium isolated from deep-sea sediment of the Yap Trench, Pacific Ocean - Xiashutong Xu; Libo Yu; Guangxin Xu; Qilin Wang; Shiping Wei; Xixiang Tang (Antonie van Leeuwenhoek, 2020)

Bionic fungicide physcion controls gray mold in tomato: possible modes of action - Libo Xiang; Minfeng Xue; Lijun Yang; Shuangjun Gong; Dazhao Yu (Journal of General Plant Pathology, 2019)

The effect of different pretreatments on the quality of ready-to-eat jellyfish Rhopilema esculentum Kishinouye products - Xiuping Dong; Xinru Fan; Yang Wang; Libo Qi; Shuang Liang; Lei Qin; Chenxu Yu; Beiwei Zhu (Fisheries Science, 2018)

A review of heavy metal pollution levels and health risk assessment of urban soils in Chinese cities - Libo Pan; Yue Wang; Jin Ma; Yu Hu; Benying Su; Guangling Fang; Lei Wang; Bao Xiang (Environmental Science and Pollution Research, 2018)

Assessments of levels, potential ecological risk, and human health risk of heavy metals in the soils from a typical county in Shanxi Province, China - Libo Pan; Jin Ma; Yu Hu; Benying Su; Guangling Fang; Yue Wang; Zhanshan Wang; Lei Wang; Bao Xiang (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Nighttime electron density enhancements at middle and low latitudes in East Asia - YanYan Zhang; LiBo Liu; YiDing Chen; Jing Liu; You Yu; Ming Li (Science China Earth Sciences, 2015)

Blood–brain barrier permeability change and regulation mechanism after subarachnoid hemorrhage - Zhiqing Li; Guobiao Liang; Teng Ma; Jingchen Li; Ping Wang; Libo Liu; Bo Yu; Yunhui Liu; Yixue Xue (Metabolic Brain Disease, 2015)

GPS detection of the coseismic ionospheric disturbances following the 12 May 2008 M7.9 Wenchuan earthquake in China - Qian Song; Feng Ding; Tao Yu; WeiXing Wan; BaiQi Ning; LiBo Liu; BiQiang Zhao (Science China Earth Sciences, 2015)

Mitochondrial Membrane Fluidity is Consistently Increased in Different Models of Huntington Disease: Restorative Effects of Olesoxime - Janett Eckmann; Laura E. Clemens; Schamim H. Eckert; Stephanie Hagl; Libo Yu-Taeger; Thierry Bordet; Rebecca M. Pruss; Walter E. Muller; Kristina Leuner; Huu P. Nguyen; Gunter P. Eckert (Molecular Neurobiology, 2014)

Prevalence and genotype distribution of human papillomavirus infection in Harbin, Northeast China - Bowen Sun; Junming He; Xiaohang Chen; Meihui He; Zhangxiu He; Yan Wang; Qinglong Shang; Libo Yu; Lanlan Wei (Archives of Virology, 2014)

Novel vitamin D 1α-hydroxylase gene mutations in a Chinese vitamin-D-dependent rickets type I patient - LIHUA CAO; FANG LIU; YU WANG; JIAN MA; SHUSEN WANG; LIBO WANG; YANG ZHANG; CHEN CHEN; YANG LUO; HONGWEI MA (Journal of Genetics, 2011)

Ionospheric total electron content variations prior to the 2008 Wenchuan Earthquake - Biqiang Zhao; Min Wang; Tao Yu; Guirong Xu; Weixing Wan; Libo Liu (International Journal of Remote Sensing, 2010)

Discoidin domain receptor 2 is associated with the increased expression of matrix metalloproteinase-13 in synovial fibroblasts of rheumatoid arthritis - Jin Su; Jiangtian Yu; Tingting Ren; Wei Zhang; Yuanqiang Zhang; Xinping Liu; Tiezheng Sun; Houshan Lu; Keiji Miyazawa; Libo Yao (Molecular and Cellular Biochemistry, 2009)

Identification of the distinct promoters for the two transcripts of apoptosis related protein 3 and their transcriptional regulation by NFAT and NFκB - Guodong Yang; Fang Yu; Haiyan Fu; Fan Lu; Bo Huang; Liyuan Bai; Zhongliang Zhao; Libo Yao; Zifan Lu (Molecular and Cellular Biochemistry, 2007)

Identification of the distinct promoters for the two transcripts of apoptosis related protein 3 and their transcriptional regulation by NFAT and NFκB - Guodong Yang; Fang Yu; Haiyan Fu; Fan Lu; Bo Huang; Liyuan Bai; Zhongliang Zhao; Libo Yao; Zifan Lu (Molecular and Cellular Biochemistry, 2007)

An observational study on the vertical distribution and synoptic variation of ozone in the arctic - Zou Han; Zhou Libo; Jian Yongxiao; Liu Yu (Advances in Atmospheric Sciences, 2002)